ANALYSIS OF AMMONIA ADSORPTION ISOTHERM ON ZEOLITE СаA (M-22) IN THE THEORY OF VOLUME SATURATION OF MICROPORES (Conferencea, 2023)
The article presents experimentally obtained values of the adsorption isotherm of ammonia molecules in synthetic zeolite SaA (M-22) at a temperature of 303 K and calculated values based on the theory of volume saturation of micropores. The isotherm of ammonia molecules in CaA (M-22) nanostructured zeolite was studied and the free energy values were calculated. Tetramer 4NH3:Na+ in the first coordination sphere with sodium cations in the SI ва SII positions of zeolite, dimer 2NH3:Са2+ ion-molecular complexes with calcium cations in the first coordination sphere, then two ammonia molecules with the initially adsorbed ammonia molecules in the second coordination sphere Са2+:2NH3:2NH3 - was found to form molecular complexes. It was proved that the mechanism based on the coefficients of the adsorption amount obtained on the basis of the volume theory of micropores fully corresponds to the mechanism based on the values obtained in the experiment. It was found that 65% of the total adsorption amount up to 50 torr corresponds to the adsorption of sodium and calcium cations, the main active centers of zeolite.